THU0428 Methotrexate Use is not Associated with an Increased Risk of Lung Disease: A Meta-Analysis of Randomised Controlled Trials. (10th June 2014) - Low, C.; Conway, R.; Coughlan, R.J.; O'Donnell, M.J.; Carey, J.J.
Abstract : Background: Methotrexate is the most widely prescribed DMARD in inflammatory arthritis, and is widely used in psoriasis and inflammatory bowel disease. A recent meta-analysis of methotrexate in rheumatoid arthritis (RA) showed that the risk of lung disease is much lower than previously thought. These results may have been affected by channelling bias as RA patients can get several forms of lung disease as a manifestation of their RA. We therefore evaluated the risk of lung disease in conditions where it is not a recognised feature of the underlying disease process. Objectives: To evaluate the relative risk of pulmonary adverse events in patients with psoriatic arthritis, psoriasis and inflammatory bowel disease treated with methotrexate in double-blind randomised controlled trials. Methods: We performed a systematic literature search of Pubmed and Cochrane databases with no date limits for double-blind randomised controlled trials of methotrexate versus placebo or active comparator agents in adults with psoriatic arthritis, psoriasis or inflammatory bowel disease. Studies with less than 50 subjects, of less than 12 weeks duration, or with no reporting of respiratory adverse events were excluded. Two investigators independently searched both databases. All authors reviewed selected studies. Random effects meta-analysis using the Mantel-Haenszel method was used to assess total respiratory adverse events, infectious respiratory adverse events, non-infectious respiratory adverse events, pneumonitis, and death. Results were expressed as relative risks (RR) with 95% confidence intervals. Results: Our literature search returned 2968 results. A total of 7 studies, 6 with placebo comparators, met our inclusion criteria. Five hundred and four respiratory adverse events were documented in 1630 participants. One case of pneumonitis was reported in a methotrexate treated patient. No pulmonary deaths occurred. Heterogeneity across the studies was not significant (I 2 =0%), allowing combination of trial results. Methotrexate was not associated with an increased risk of adverse respiratory events, RR 1.03 (95% CI 0.90-1.17), respiratory infections, RR 1.02 (95% CI 0.88-1.19) or non-infectious respiratory events, RR 1.07 (95% CI 0.58-1.96). Subgroup analysis is shown in Table 1 . Conclusions: Our study found no increased risk of pulmonary adverse events in patients treated with methotrexate compared to placebo or active comparators. There were a small number of suitable studies but our results suggest that if adverse respiratory events occur with methotrexate use they are rare. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.1801